'Activity-silent' working memory in prefrontal cortex: a dynamic coding framework. Issue 7 (July 2015) - Stokes, Mark G.
Highlights: WM is thought to depend on persistent maintenance of stationary activity states. However, population-level analyses reveal that brain activity is highly dynamic. Accumulating evidence implicates activity-silent neural states for WM. Dynamic coding suggests that WM is encoded in patterns of functional connectivity. Abstract : Working memory (WM) provides the functional backbone to high-level cognition. Maintenance in WM is often assumed to depend on the stationary persistence of neural activity patterns that represent memory content. However, accumulating evidence suggests that persistent delay activity does not always accompany WM maintenance but instead seems to wax and wane as a function of the current task relevance of memoranda. Furthermore, new methods for measuring and analysing population-level patterns show that activity states are highly dynamic. At first glance, these dynamics seem at odds with the very nature of WM. How can we keep a stable thought in mind while brain activity is constantly changing? This review considers how neural dynamics might be functionally important for WM maintenance.